Magnetic Field Turbulence in the Solar Wind at Sub‐ion Scales: In Situ Observations and Numerical Simulations - Matteini, L.; Franci, L.; Alexandrova, O.; Lacombe, C.; Landi, S.; Hellinger, P.; Papini, E.; Verdini, A. (Frontiers in Astronomy and Space Sciences, 2020)
We investigate the transition of the solar wind turbulent cascade from MHD to sub-ion range by means of a detail comparison between in situ observations and hybrid numerical simulations. In particular we focus on the properties of the magnetic field and its component anisotropy in Cluster measurements and hybrid 2D simulations. First, we address the angular distribution of wave-vectors in the kinetic range between ion and electron scales by studying the variance anisotropy of the magnetic field components. When taking into account the single-direction sampling performed by spacecraft in the solar wind, the main properties of the fluctuations observed in situ are also recovered in our numerical description. This result confirms that solar wind turbulence in the sub-ion range is characterized by a quasi-2D gyrotropic distribution of k-vectors around the mean field. We then consider the magnetic compressibility associated with the turbulent cascade and its evolution from large-MHD to sub-ion scales. The ratio of field-aligned to perpendicular fluctuations, typically low in the MHD inertial range, increases significantly when crossing ion scales and its value in the sub-ion range is a function of the total plasma beta only, as expected from theoretical predictions, with higher magnetic compressibility for higher beta. Moreover, we observe that this increase has a gradual trend from low to high beta values in the in situ data; this behaviour is well captured by the numerical simulations. The level of magnetic field compressibility that is observed in situ and in the simulations is in fairly good agreement with theoretical predictions, especially at high beta, suggesting that in the kinetic range explored the turbulence is supported by low-frequency and highly-oblique fluctuations in pressure balance, like kinetic Alfvén waves or other slowly evolving coherent structures. The resulting scaling properties as a function of the plasma beta and the main differences between numerical and theoretical expectations and in situ observations are also discussed.